Supporting people on fighting lesbian, gay, bisexual, and transgender (LGBT) prejudice: a critical codesign process - Pereira, Guilherme C. Pereira; Baranauskas, M. Cecilia C. Baranauskas (Teste; 2018: IHC_21, 2018)
Lesbian, gay, bisexual, and transgender (LGBT) people face a range of daily struggles, including those experienced through digital media. Such issues are increasingly gaining space in software development and academia agendas. This paper addresses the subject by first providing a systematic review for both academic and mobile technical productions towards LGBT people, identifying some tendencies and opportunities. Then we show how such results have been influencing the outcome of an ongoing research which aims to build a tool to help prevent and fight prejudice against LGBT people in Brazil. Results of a critical codesign process are presented and discussed showing evidences of the methodology adequacy.